Inter-rater agreement of CDC criteria and ASEPSIS score in assessing surgical site infections after cesarean section: a prospective observational study - Delli Carpini, Giovanni; Giannella, Luca; Di Giuseppe, Jacopo; Fioretti, Marco; Franconi, Ilaria; Gatti, Ludovica; Sabbatini, Keti; Montanari, Michele; Marconi, Chiara; Tafuri, Elisa; Tibaldi, Luisa; Fichera, Mariasole; et al. (Frontiers in Surgery, 2023)
To assess and compare the inter-rater agreement of the CDC criteria and the ASEPSIS score in identifying surgical site infections after cesarean section.Prospective observational study including 110 patients subjected to a cesarean section at our institution. Surgical wounds were managed according to standard care and were photographed on the third, seventh, and thirtieth postoperative day or during any evaluation in case of complications. Three expert surgeons reviewed the prospectively gathered data and photographs and classified each wound using CDC criteria and the ASEPSIS score. The inter-rater agreements of CDC criteria and ASEPSIS score were determined with Krippendorff's Alpha with linear weights and compared with a confidence interval approach.The weighted α coefficient for CDC criteria was 0.587 (95%CI 0.411-0.763, p<0.001, "moderate" agreement according to Altman's interpretation of weighted agreement coefficient), while the weighted α coefficient for the ASEPSIS score was 0.856 (95%CI 0.733-0.980, p<0.001, "very good" agreement).ASEPSIS score presents a "very good" inter-rater agreement for surgical site infections identification after cesarean, resulting in a more objective method than CDC criteria ("moderate" inter-rater agreement). ASEPSIS score could represent an objective tool for managing and monitoring surgical site infections after cesarean section, also by photographic evaluation.